Sedation, temperature and pressure after cardiac arrest and resuscitation-The STEPCARE trial: A statistical analysis plan - Kamp, C B; Dankiewicz, J; Harboe Olsen, M; Holgersson, J; Saxena, M; Young, P; Niemelä, V H; Hästbacka, J; Levin, H; Lilja, G; Moseby-Knappe, M; Tiainen, M; et al. (Acta anaesthesiologica Scandinavica, 2025)
BACKGROUND: Basic management for patients who have suffered a cardiac arrest and are admitted to an intensive care unit (ICU) after resuscitation includes setting targets for blood pressure and managing sedation and temperature. However, optimal targets and management are unknown. METHODS: The STEPCARE (Sedation, Temperature and Pressure after Cardiac Arrest and Resuscitation) trial is a multicenter, parallel-group, randomized, factorial, superiority trial in which sedation, temperature, and blood pressure strategies will be studied in three separate comparisons (SED-CARE, TEMP-CARE, and MAP-CARE). The trial population will be adults admitted to intensive care who are comatose after resuscitation from out-of-hospital cardiac arrest. The primary outcome will be all-cause mortality, and the secondary outcomes will be poor functional outcome (modified Rankin Scale 4-6), Health-Related Quality of Life using EQ-VAS, and specific serious adverse events in the intensive care unit predefined for each trial. All outcomes will be assessed at 6 months after randomization. The prognosticators, outcome assessors, statisticians, data managers, steering group, and manuscript writers will be blinded to treatment allocation. This statistical analysis plan includes a comprehensive description of the statistical analyses, handling of missing data, and assessments of underlying statistical assumptions. Analyses will be conducted according to the intention-to-treat principle, that is, all randomized participants with available data will be included. The analyses will be performed independently by two statisticians following the present plan. CONCLUSION: This statistical analysis plan describes the statistical analyses for the STEPCARE trial in detail. The aim of this predefined statistical analysis plan is to minimize the risk of analysis bias.
Keywords: Humans; statistical analysis; Cardiopulmonary Resuscitation; STEPCARE trial; sedation; Quality of Life; lidé; kardiopulmonální resuscitace; randomizované kontrolované studie jako téma; kvalita života; krevní tlak; Randomized Controlled Trials as Topic; Body Temperature; cardiac arrest; zástava srdce mimo nemocnici; tělesná teplota; Out-of-Hospital Cardiac Arrest; blood pressure; Blood Pressure; temperature